The Safety and Efficacy of the Repeated PRRT with [90Y]Y/[177Lu]Lu-DOTATATE in Patients with NET - Anna Zemczak; Paweł Gut; Dariusz Pawlak; Maciej Kołodziej; Leszek Królicki; Beata Kos-Kudła; Marek Ruchała; Grzegorz Kamiński; Jolanta Kunikowska (International Journal of Endocrinology)
Purpose. The peptide receptor radionuclide therapy (PRRT) is a treatment option for patients with disseminated, inoperable G1 and G2 neuroendocrine tumours (NETs). The study aims to evaluate the safety, efficacy, and progression-free survival (PFS) of patients after retreatment (R-PRRT) and re-retreatment (RR-PRRT) with tandem isotopes [90Y]Y/[177Lu]Lu-DOTATATE. Material and Methods. Out of 99 treated patients with G1 and G2 NETs, 26 were included in the study and treated with the repeated PRRT (with 5 undergoing the re-repeated PRRT treatment) after an initial positive response to four PRRT cycles and later progression of the disease. [68Ga]Ga-DOTATATE PET/CT and CT/MRI procedures were performed before and after the treatment. Patients were treated with [90Y]Y/[177Lu]Lu-DOTATATE (1 : 1) with mixed amino acid infusion for kidney protection. Toxicity was evaluated using the CTCAE 3.0 criteria. Results. The median follow-up was 88 months (the range: 42–164). The median cumulative administered activity was 22.2 GBq (the range: 17.8–30.7 GBq). Myelodysplastic syndrome occurred in one patient (3.8%), and grade 4 renal toxicity was also detected in one patient (3.8%). No other cases of grade 3 or 4 bone marrow and renal toxicity were observed. The median PFS rate was 31 months after the PRRT and 23 months following the R-PRRT. The OS rate from the diagnosis (OS-d) was 109 months and from the start of the PRRT (OS-t)-92.4 months. During the restaging, 3–6 months after the PRRT, PR, SD, and PD were observed in 19.2%, 80.8%, and 0% of the patients, respectively. After the R-PRRT, PR, SD, and PD were observed in 50%, 42.3%, and 7.7% of the patients, respectively. Conclusions. The repeated therapy with [90Y]Y/[177Lu]Lu-DOTATATE is safe and effective for patients with disseminated, inoperable G1 and G2 neuroendocrine tumours.